A Novel Fluorescent Dye Invades Mitochondria to Selectively Kill Cancer Stem Cells via Increased ROS Production - Bei-Bei Zhang; Jun-gang Liu; Xian-Yu Bai; Yuan-Jiao Huang; Ning Xu; Tao Ren (Bioinorganic Chemistry and Applications)
Development of multiple agents has a significant impact on the cancer diagnosis and therapy. Several fluorescent dyes including near-infrared (NIR) fluorescent agents have been already well studied in the field of photodynamic therapy (PDT). In the present study, we reported a novel fluorescent dye could obviously inhibit cancer cell proliferation with slight toxic effects on the biological organism. Furthermore, it displayed selective staining on cancer cells, particularly on cancer stem cells (CSCs), rather than normal cells. Mechanically, this dye preferred to invading mitochondria of cancer cells and inducing overwhelming reactive oxygen species (ROS) production. The in vivo experiments further demonstrated that this dye could image cancer cells and even CSCs in a short-time intratumor injection manner using a zebrafish model and subsequently inhibit cancer cell proliferation after a relatively long-time drug exposure. Taken together, the future development of this agent will promise to make an essential contribution to the cancer diagnosis and therapeutics.